2013
DOI: 10.1002/cncy.21346
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for increasing usage of low‐grade squamous intraepithelial lesion, cannot exclude high‐grade squamous intraepithelial lesion (LSIL‐H) Pap test interpretations

Abstract: BACKGROUND: Pap test (PT) interpretations of low-grade squamous intraepithelial lesion (LSIL), cannot exclude high-grade squamous intraepithelial lesion (HSIL), or LSIL-H, are used in many laboratories; however monitoring its usage for quality assurance purposes is understudied. METHODS: PTs from 2005 to 2010 were collected, and yearly frequencies of LSIL, HSIL, LSIL-H, and atypical squamous cells, cannot exclude HSIL (ASC-H) as a function of total PTs and total squamous intraepithelial lesions (SILs) were cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…A publication based on a 2011 CAP survey showed that 80.9% of laboratories were using LSIL-H to report such specimens. 1 Although many papers in the literature have reported use of the LSIL-H category, [15][16][17][18][19] for TBS 2014, this term was considered but not endorsed. Instead, TBS 2014 recommends that such cases be interpreted as ASC-H with a comment that LSIL is also present.…”
Section: Discussionmentioning
confidence: 99%
“…A publication based on a 2011 CAP survey showed that 80.9% of laboratories were using LSIL-H to report such specimens. 1 Although many papers in the literature have reported use of the LSIL-H category, [15][16][17][18][19] for TBS 2014, this term was considered but not endorsed. Instead, TBS 2014 recommends that such cases be interpreted as ASC-H with a comment that LSIL is also present.…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, LROH comprised only 0.30% of all Pap tests evaluated during the study interval which are comparable with previously reported rates. For example, Alsharif et al reported the rate as 0.35%, Walavalkar et al reported 0.41%, Shidham et al reported a 0.19% rate, Elsheikh et al reported 0.15%, Barron et al reported a 0.18% rate and Owens et al reported 0.50%.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, LROH diagnosis is used in our practice in cases with unequivocal LSIL showing cells suggesting HSIL, which are insufficient, either qualitatively or quantitative for a definitive HSIL diagnosis, as well as other features described in literature . A common scenario includes the presence of few hyperchromatic crowded groups, atypical keratinised cells or scattered small squamous cells with increased nuclear to cytoplasmic ratio, variable nuclear hyperchromasia and nuclear membranes irregularities in a background of LSIL (Figure ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation